PENGARUH PENDIDIKANKESEHATAN TENTANG 3M TERHADAP SIKAP KELUARGA DALAM PENCEGAHAN DEMAM BERDARAH( STUDY ANALITIK DI LINGKUNGAN BENCE RT 24 RW 05KELURAHAN PAKUNDEN KOTA KEDIRITAHUN 2008 ) - Agustina, Emi; Suryono, Suryono; Setiawan, Andika Bagus (Akademi Keperawatan Pamenang, 2010)
Education of health is process to increase ability of society in looking after and improving its health. Attitude notyet represented an activity or action however representing open or open behaviour. Target of this research is toknow what is there influence of gift education of health about 3 M to society attitude in prevention of dengue inenvironment of Bence Sub-District of Pakunden. Desain Research weared in this is analytic. Its population is theoverall of family head exist in RT 24 RW 05. Sample of is over all of population taken with sampling purposivecounted 30 client. Data processed by using statistical test of Wilcoxon Signed Rank Test. With result of from 15responder getting treatment which before education of health only getting value enough there is 11 responder (73,3 ) and less there is 4 responder ( 26,7 ) but after can education of health 15 natural responder [is] make-upof change become goodness there is 12 responder ( 80 ) and enough there is 3 responder ( 20 ). From result ofresearch with test of statistic the Wilcoxon Signed Ranks Test got by P signifikasi = 0,002 with = 5 = 0,05.Becoming there by H0 = Refused by becausevalue of P < 0,05. Equally there is influence of education of healthabout 3 M to family attitude in prevention of dengue. One of them is to education of health about 3 M, previousfamily have attitude which enough or less after getting education of healthcan turn into betterly. Family becomediffraction understand hygiene of environment will and also can do prevention of dengue self-supportingly